2016
DOI: 10.1002/we.1987
|View full text |Cite
|
Sign up to set email alerts
|

Geographic aggregation of wind power-an optimization methodology for avoiding low outputs

Abstract: This work investigates macro-geographic allocation as a means to improve the performance of aggregated wind power output. The focus is on the spatial smoothing effect so as to avoid periods of low output. The work applies multiobjective optimization, in which two measures of aggregated wind power output variation are minimized, whereas the average output is maximized. The results show that it is possible to allocate wind power so that the frequency of low outputs is substantially reduced, while maintaining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…There is also a large amount of literature on the effects of geographic dispersion on aggregate wind power. Reichenberg et al [19] considered Europe as whole with an assumed rather than actual arrangement of wind farms. They showed that it was possible to optimize the layout to minimize, for example, occurrences of low aggregate power.…”
Section: Applicationsmentioning
confidence: 99%
“…There is also a large amount of literature on the effects of geographic dispersion on aggregate wind power. Reichenberg et al [19] considered Europe as whole with an assumed rather than actual arrangement of wind farms. They showed that it was possible to optimize the layout to minimize, for example, occurrences of low aggregate power.…”
Section: Applicationsmentioning
confidence: 99%
“…However, for the preparation step (integral or representative days method), the demand data are normalised so that the maximum demand event is given a value of 1. The wind and solar data input is based on weather data from the European Centre for Medium-Range Weather Forecasts (ECMWF), processed through a turbine function and a function to mimic the output of solar PV (see Reichenberg et al (2017) for a more thorough description). Solar and wind output also attain values between 0 and 1, but 1 is equivalent to the nameplate capacity.…”
Section: Datamentioning
confidence: 99%
“…Drake and Hubacek, Roques et al, and Thomaidis et al use the total standard deviation for the wind portfolio selected. Cassola et al and Reichenberg et al use different variants of a metric measuring the total stepwise change of energy output over time. We use a similar metric, specifically the average absolute difference in residual demand between each consecutive pair of time periods, as our variability metric in one of the two model variants.…”
Section: Introductionmentioning
confidence: 99%
“…None of these metrics give proper weight to extreme changes in wind power, which, as Dowds et al point out, is the primary risk to system reliability when incorporating wind power. Recognizing the importance of extremities, Grothe and Schnieders and Reichenberg et al seek to minimize the value at risk and conditional value at risk, respectively. However, these metrics only measure the probability of low wind power output rather than capturing sudden extreme fluctuations in wind.…”
Section: Introductionmentioning
confidence: 99%